Medical waste management in Khulna City Corporation, Bangladesh - Jeba, Jafrin Sultana; Rahman, Md. Mujibor (National Geographical Journal of India, 2022)
Management of medical waste or Clinical Solid Waste(CSW) is a major challenge for developing world and poor countries. In a developing country like Bangladesh, poor and inappropriate handling of medical waste continuously increases health risks, as well as environmental risks thus treatment and management of Health-Care Waste (HCW), are important here. This study reviews the current situation of medical waste management (MWM) and practices in Khulna City Corporation, Bangladesh, and examines possible solutions for further study. Both qualitative and quantitative data were used in this study. The study was conducted in 30 HCEs (Health Care Establishments) within Khulna City Corporation. The Result of the study unveiled an unsatisfactory management system in the surveyed HCEs.The entire city corporation's waste management is looked after through a public-private partnership between City Corporation and Prodipan(NGOs). Everyday 3509kg wastes are generated from HCEs within the City Corporation. Only 28% of the waste handling process related personnel claimed that they got training, none of this HCEs has their waste transportation (off-site transportation) facilities and for waste management, they entirely depend on City Corporation and Prodipan. For waste management, absence necessary plan and monitoring team makes it more difcult, only 33% of the surveyed HCEs showed their satisfaction for their manpower in this sector. Only 3.3% Health-Care Establishments (HCEs) have claimed that they have their distinguished treatment facilities for specic non-hazardous wastes. Insufcient collection and storage facilities, inadequate transportation and disposal facilities. The nding also demonstrates that segregation practices were not satisfactory in public and small HCEs. Arrangement of training and awareness program, appropriate plan, skilled staffs, proper storage facilities, regular monitoring are recommended to achieve an efcient medical waste management system.